2008
DOI: 10.1152/japplphysiol.00954.2007
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine responses to acute and chronic exercise in multiple sclerosis

Abstract: Regular exercise reduces functional loss associated with multiple sclerosis (MS). However, the impact of exercise on inflammatory mediators associated with disease activity remains relatively unexplored. The purpose of this study was to determine whether ambulatory MS subjects would respond similarly to aerobic cycle training compared with matched controls on circulating immune variables, interleukin (IL)-6, tumor necrosis factor (TNF)-alpha and interferon (IFN)-gamma. Eleven MS and 11 non-MS control subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
95
1
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(107 citation statements)
references
References 37 publications
5
95
1
6
Order By: Relevance
“…There is extensive research dealing with the specific response of different exercise regimes in relation of age, gender, training status, and physical conditions including obesity and diverse chronic inflammatory disorders [3][4][5][6][7][8][9]. Most of these studies focus on exercise-induced responses of selected plasma cytokines altered by acute exercise stimuli [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…There is extensive research dealing with the specific response of different exercise regimes in relation of age, gender, training status, and physical conditions including obesity and diverse chronic inflammatory disorders [3][4][5][6][7][8][9]. Most of these studies focus on exercise-induced responses of selected plasma cytokines altered by acute exercise stimuli [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Despite the demonstrated benefits, attrition in exercise intervention studies is a concern, ranging from just over 18% 6 to 42%. 4 These high attrition rates bring into question the feasibility of exercise programs ized so as to minimize physical and mental fatigue by allowing adequate rest periods.…”
mentioning
confidence: 99%
“…Golzari, Shabkhiz, Soudi, Kordi & Hashemi, 2010;Castellano, Patel & White, 2008) showed that physical activity improves patients' clinical symptoms while the result of (Bjarnadottir, Konradsdottir, Reynisdottir & Olafsson, 2007) was opposed. Golzari et al (2010) examined the effect of 24 sessions combined exercise training over eight weeks on 20 MS patients between the ages of 20 and 50 with disability status scale (EDSS) of 0-4.…”
Section: Discussionmentioning
confidence: 99%